Basics and Applications of STATA Software: A Virtual Training for ACIAR Project Data Management and Analysis - Mekuriaw, Shigdaf; Dijk, Suzanne V; Tesfa, Assemu; Opiyo, Joseph; Makonnen, Brook T. (International Livestock Research Institute, 2025)
The International Livestock Research Institute (ILRI), through the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA), and in collaboration with UNIQUE Land Use and the Food, Agriculture and Natural Resources Policy Analysis Network (FANRPAN), implementing a project focusing on "Strengthening Adaptive Capacity of Extensive Livestock Systems for Food and Nutrition Security and Low-emissions Development in Eastern and Southern Africa (ESA)." The Australian Centre for International Agricultural Research (ACIAR) funds the project. The project aims to support stakeholders engaged in extensive livestock systems in ESA in designing and implementing scalable, sustainable interventions that promote the adaptive capacity and food and nutrition security of men and women livestock keepers, while reducing greenhouse gas emissions (GHG) from livestock production. The focus countries include Ethiopia, Kenya, and Zimbabwe. In Ethiopia, the ACIAR project focuses on the impact of livestock interventions on greenhouse gas emissions and adaptive capacity. Thus, in November 2024, capacity-building training was prepared on the Basics and Application of STATA software for ACIAR project data management and analysis, specifically for Strengthening Adaptive Capacity of Extensive Livestock Systems (Virtually), for ACIAR project-funded students, supervisors, partners, and relevant stakeholders.